PREPARATION OF SALBUTAMOL SULPHATE LOADED LOCUST BEAN GUM-POLYVINYL ALCOHOL COMPOSITE CRYOGEL FOR DRUG DELIVERY - RAINA, NEHA; BHATIA, MEENAKSHI; PAHWA, RIMPY; PAHWA, RAKESH; GUPTA, MADHU; KUMAR, MANISH (International Journal of Applied Pharmaceutics, 2022)
Objective: The key goal of the experimental study involves the preparation of salbutamol sulphate drug-loaded freeze thawed composite cryogels, comprising locust bean gum and polyvinyl alcohol and evaluating them for drug delivery. Methods: The cryogels were formulated using freeze thaw process and characterization was performed using numerous techniques like Fourier transform-infrared spectroscopy, differential scanning calorimetry, scanning electron microscopy, X-ray diffraction studies, swelling behaviour and in vitro drug release. Results: FTIR spectra of drug loaded LBG-PVA composite cryogels showed sharp peak at 3437 cm-1 owing to O-H stretching of free hydroxyl groups. DSC thermogram of LBG-PVA composite cryogels displayed a broad endotherm with hump at 190.85 °C. XRD analysis of LBG-PVA composite cryogel indicated characteristic peak at 19.83° (2θ) which suggest that formation of cryogels between two polymers contributes to a decrease in crystallinity. SEM analysis depicted that LBG-PVA composite cryogels were porous in nature as interconnected and irregular pores with thick walls. Swelling study inferred that on increasing the concentration of both polymers the swelling ability of LBG-PVA increased considerably. Results obtained from optimization study suggested that greater concentration of both locust bean gum and polyvinyl alcohol favoured release of salbutamol sulphate in a sustained manner. The experimental findings display in vitro release of salbutamol sulphate as 77.75% over duration of 24 h following Higuchi’s square root release kinetics. Conclusion: The outcomes of the experimental investigation depicted that locust bean gum in combination with polyvinyl alcohol favoured synergistically with release of salbutamol sulphate in a sustained manner.